Studying the spatio-temporal changes of urban green space: A case study of Pokhara Metropolitan City - Subedi, Sandip; Pokhrel, Shiva (Journal of Engineering Issues and Solutions, 2023)
Green space refers to land areas covered primarily with vegetation, including parks, gardens, nature reserves, and other similar areas. These spaces offer various benefits such as supporting biodiversity, enhancing air and water quality, promoting mental and physical well-being, providing opportunities for recreation and social interaction, and improving the overall beauty of the environment. To assess the dynamics of green space in Pokhara Metropolitan City (PMC), maximum likelihood classification and normalized difference vegetation index (NDVI) methods were utilized to analyze satellite imagery. The study showed two distinct patterns of urban green space, with the green space in the central city gradually decreasing, while the nearby suburban and remote areas of PMC experienced an increase as agricultural land was transformed into grassland due to population migration. Consequently, the area of moderately healthy vegetation increased, while healthy vegetation decreased from 4926 hectares (10.61% of total area) to 2535 hectares (5.46% of total area). Additionally, the area of no vegetation such as urban areas increased from 1.8% to 2.17%. An accuracy assessment was used to validate the analyzed data, resulting in an overall accuracy of 81.91% and a Kappa coefficient of 0.63. The primary factors contributing to the loss of green spaces were urban growth and population growth within the inner metropolis. Therefore, it is crucial to maintain PMC's green areas and give more attention to this issue while developing municipal plans and policies in the future.